Kemampuan Menulis Teks Laporan Hasil Observasi Menggunakan Teknik Show Not Tell Siswa Kelas X SMAN 1 Sampolawa Kabupaten Buton Selatan - Herni, Wa; Daeng, Kembong; Haliq, Abdul (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the ability to write observation report texts using the show not tell technique of class X students of SMAN 1 Sampolawa, South Buton Regency. This study uses a descriptive method with a quantitative approach. The population of this study, namely all class X students of SMAN 1 Sampolawa, South Buton Regency, totaling 87 students. Sampling used a simple random sampling technique with a sample size of 30 students. The data collection technique used an assignment technique, namely students were given the task of writing texts with an allocation of 80 minutes. The technique used in analyzing the data was descriptive statistics by calculating the average value. The results showed that the average value of the ability to write observation report texts using the show not tell technique was 74 in the capable category. This was evidenced by the value obtained, namely 21 students were included in the capable category with a value interval of 70-100 and 9 students were included in the incapable category with a value interval of ≤55-69. So, it can be concluded that class X students of SMAN 1 Sampolawa are able to write observation report texts by expressing ideas, explaining each part that forms the structure of the text based on the observation results.